ANALISIS BELANJA DAERAH PEMERINTAH KOTA PROBOLINGGO - Wulandari, Nurfifah; Anggono, Alexander (LPPM Universitas Bina Bangsa, 2025)
Regional autonomy depends on how local governments manage their finances effectively, efficiently, orderly, economically, transparently and responsibly. Regional expenditure is divided into three, namely operating expenditure, capital expenditure and unexpected expenditure. The purpose of this study is to determine the financial performance of the local government of Probolinggo City by analyzing regional expenditure in the last 3 years, namely 2021 - 2023. This research uses a quantitative descriptive method. By using secondary data from the Probolinggo City APBD Realization Report for 2021 - 2023. The data obtained is processed using a previously provided formula and then analyzed using the expenditure variance ratio, expenditure compatibility ratio and regional expenditure efficiency ratio. The results of this study are a variance ratio of 85.76, a ratio of compatibility of operating expenditure and capital expenditure of 84% and 14.43%, a spending efficiency ratio of 85.76%. From the percentage of these ratios shows that Probolinggo City performs financial performance well seen from the efficiency of budget use and expenditure savings. However, operating expenditures tend to be higher than capital expenditures.